PEMIKIRAN POLITIK PADA MASA KHULAFAUR RASYIDIN - Adelia Ramzar; Muhammad Hidayat Harahap; Tengku Nazib Ahmad Kamil (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The Khulafaur Rasyidin era (632–661 CE) was a pivotal period in Islamic history, marked by the leadership of the first four caliphs: Abu Bakr, Umar, Uthman, and Ali. The political thought of this era emphasized principles of justice, consultation (shura), and the application of Islamic law (sharia) in governance. Each caliph adopted distinct approaches to state administration, such as Abu Bakr's emphasis on collective consultation and Umar's establishment of a more bureaucratic governance structure. Despite political and social challenges, including territorial expansions and internal conflicts, the political foundations of the Rashidun Caliphate underscored the importance of just leadership and the unity of the Muslim community. This political philosophy significantly contributed to the development of Islamic governance rooted in justice and sharia.